PENGARUH STRATEGIC DECISION MAKING SEBAGAI STRATEGIC MANAGEMENT ACCOUNTING TECHNIQUES TERHADAP COMPETITIVE ADVANTAGE DAN ORGANIZATIONAL PERFORMANCE - Monica, Sienatra (Business Accounting Review, 2015)
The aim of this study is to determine and examine the effect Strategic Decision Making to Organizational Performance through Competitive Advantage as an intervening variable. Samples in this study are manufacturing companies located in Surabaya and Sidoarjo. The data used in this research was primary data in the form of a questionnaire that was distributed to 50 manufacturing companies in Surabaya and Sidoarjo. Hypothesis testing in this study will be carried out by using path analysis modeling techniques through PLS program. The test results stating that there is a positive and significant effect of Strategic Decision Making on Competitive Advantage, Strategic Decision Making on Organizational Performance and Competitive Advantage on Organizational Performance.